Comparative Study of Elementary School Student’s Mathematics Learning Motivation In Offline And Online Learning - Falatah, Fachri Akbar; Nabila, Kafka; W, Wahyunengsih (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study compares elementary school students motivation to learn mathematics in offline face-to-face) and online (online) learning. The method used is a quantitative approach with a comparative design. The sample in this study were students in grades IV and V from one elementary school who implemented learning in the two models. Data were collected through a validated learning motivation questionnaire and analyzed using the t-test. The results of the study showed that students learning motivation in offline learning was higher than in online education. Factors influencing this difference include the intensity of interaction with the teacher, the classroom atmosphere, and the students ability to manage their time independently. This study recommends adaptive and interactive learning strategies in online learning, especially for elementary school students who still need intensive guidance.